2001
DOI: 10.1021/jp0045437
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Mode Assignments of Jet-Cooled m-Chlorobenzyl Radical in the Ground Electronic State

Abstract: The jet-cooled m-chlorobenzyl radical has been generated for the first time from m-chlorotoluene with a large amount of carrier gas He in a corona excited supersonic expansion using a pinhole-type glass nozzle. The visible vibronic emission spectrum of the m-chlorobenzyl radical in the transition of D 1 f D 0 has been recorded with a long path monochromator. The spectrum has been analyzed to obtain the accurate electronic transition and vibrational mode frequencies in the ground electronic state by comparing w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 26 publications
1
26
1
Order By: Relevance
“…The 2,5-dichlorobenzyl radical exhibits larger shift than expected from those of 2-and 3-chlorobenzyl radicals because the molecule has two Cls at the 2-and 3-positions. For chlorobenzyl radicals, 2-, 3-, and 4-substitutions [7][8][9] shift the origin bands to red region by 962, 808, and 357 cm À1 , respectively, from that of the benzyl radical at 22 002 cm À1 , as listed in Table 1. The trend is similar to that observed for methylbenzyl radicals, reflecting similar symmetry in the D 1 state.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The 2,5-dichlorobenzyl radical exhibits larger shift than expected from those of 2-and 3-chlorobenzyl radicals because the molecule has two Cls at the 2-and 3-positions. For chlorobenzyl radicals, 2-, 3-, and 4-substitutions [7][8][9] shift the origin bands to red region by 962, 808, and 357 cm À1 , respectively, from that of the benzyl radical at 22 002 cm À1 , as listed in Table 1. The trend is similar to that observed for methylbenzyl radicals, reflecting similar symmetry in the D 1 state.…”
Section: Resultsmentioning
confidence: 88%
“…Hamatani et al [6] extended the study to other isomers and measured lifetimes at the excited electronic states. In another study [7][8][9], extended vibronic assignments of isomeric chlorobenzyl radicals were achieved from observation of vibronic emission spectra using plasma discharge of chlorotoluenes.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, many different types of fluorine-substituted benzyl-type radicals were confirmed by corona discharge of the precursors. 4,[12][13][14][15] Although chlorine-substituted benzyl-type radicals have been recognized to emit much weaker fluorescence in the electronic transition, chlorobenzyl radicals have been investigated through vibronic emission spectra observed with CESE [16][17][18] and laserinduced fluorescence techniques. 19 However, the study on multi-chlorine substituted benzyl radicals has remained very limited because of their characteristics of weak intensity with increasing number of chlorine atoms in the benzene ring.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] Weakly emitting chlorobenzyl radicals have been recently identified from the vibronic emission spectra, in which the sequence of electronic energy of the lowest excited electronic state exhibits similar tendency to those of chlorotoluenes. [12][13][14][15][16] Cyanobenzyl radicals are also interesting species in spectroscopy due to the electron-rich substituent. The analysis of the vibronic bandshape of the p-cyanobenzyl radical has revealed that the lowest excited electronic state is 2 B 2 which is different from other types of benzyl radicals.…”
mentioning
confidence: 99%